2021
DOI: 10.35808/ijeba/696
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Marketing Strategy of Micro, Small and Medium Enterprises in Pandemic Covid-19 Era

Abstract: Purpose:The Indonesian economy's core strength comes from micro, small and medium enterprises (MSMEs). However, the impact of the Covid-19 pandemic causes problems for MSMEs, for example, decreased sales, difficulties in financial aspects, slow distribution of products, and raw materials shortage. The problems of MSME during the Covid-19 pandemic require entrepreneurs' readiness to survive and sustain their business. Entrepreneurial marketing is a suitable paradigm to be implemented by MSME entrepreneurs durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Empirical statistical research was carried out on large samples using statistical techniques. The studies in this category were applied in private business and investigated the characteristics of companies and entrepreneurs [12,[71][72][73][74][75], customer relations [76], success factors [27,77,78], determinants of business survival [9,23,[77][78][79], factors that contributed to failure [15][16][17][80][81][82], and factors related to the performance of MSEs [19,24,[83][84][85][86]. Organizational difficulties in management involving finance [21,[87][88][89][90][91][92], environmental sector [93][94][95], quality systems [96], supply chain [97], innovation [3,[98][99][100][101][102][103]…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Empirical statistical research was carried out on large samples using statistical techniques. The studies in this category were applied in private business and investigated the characteristics of companies and entrepreneurs [12,[71][72][73][74][75], customer relations [76], success factors [27,77,78], determinants of business survival [9,23,[77][78][79], factors that contributed to failure [15][16][17][80][81][82], and factors related to the performance of MSEs [19,24,[83][84][85][86]. Organizational difficulties in management involving finance [21,[87][88][89][90][91][92], environmental sector [93][94][95], quality systems [96], supply chain [97], innovation [3,[98][99][100][101][102][103]…”
Section: Descriptive Analysismentioning
confidence: 99%
“…They found that human resources were a key factor in the performance and success of SMEs (Hernita, Surya, Perwira, Abubakar, & Idris, 2021). Hadiyati and Hendrasto (2021) added that in this Covid-19 pandemic era, reliable, knowledgeable human resources are key because they provide creative and innovative ideas for a small business to survive and grow (Hadiyati & Hendrasto, 2021). This was also confirmed again by Abdulaal and Nordin (2020) who found that creativity and innovation can be expected from quality human resources, (Abdulaal & Nordin, 2020).…”
Section: Explanation : Column C Refers To Religious Figurinementioning
confidence: 88%
“…According to García-Villagrán et al (2020), during the Covid-19 pandemic, SMEs were encouraged to innovate by utilizing existing information technologies for marketing, promotion and payment systems, improving communication with consumers, building networks (networking), and partnerships, both with fellow SMEs, industry and government (García-Villagrán, Cano-Olivos, Martínez-Flores, & Sánchez-Partida, 2020) Hadiyati and Hendrasto (2021) added that during the Covid-19 pandemic, the Indonesian government provided assistance to SMEs in the form of a policy of delaying loan repayment and encouraging domestic product consumption to stimulate SMEs to produce substitutes for imported products (Hadiyati & Hendrasto, 2021). As a result, SMEs have played an important role in the economic development of communities both during and post-Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Dalam kegiatan penyuluhan, pemateri memperkenalkan Google Bisnisku sebagai salah satu platform dalam digital marketing. Selain itu pemateri juga memperkenalkan penggunaan media sosial dan e-commerce seperti CMS Wordpress, Facebook, Instagram dan marketplace (Shopee, Lazada dan Tokopedia) (Hadiyati & Hendrasto, 2021). Kegiatan ini merupakan upaya serupa sebagaimana dilaksanakan oleh (Satria, 2018;Supriyanto et al, 2021;Susanto et al, 2020).…”
Section: Pendahuluanunclassified